Morphophonemic Analysis in Children's Language (Youjigo) in The Gakuen Babysitters Manga (Vol. 1-3) - Nur Rahmi Fauzah, Nunik; Luthfiyah Ghin, Virgy; Maulani, Septi Ayu (Sinergi International Journal of Education, 2024)
This research discusses word formation in children's language variety (youjigo) in the Gakuen Babysitters manga (Volumes 1-3) through a morphophonemic review. The study aims to describe the word formation and morphophonemic processes in the children's language variety. Tsujimura's theory and Suzuki's theory are applied. The descriptive qualitative method is used with data sourced from conversations of toddler characters. Data were collected using the listen closely and take notes method and classified by morphophonemic processes. Results show 12 findings of youjigo words, primarily formed through borrowing. The morphophonemic process includes phoneme release (2), phoneme abbreviation (2), phoneme change (4), phoneme addition (2), and phoneme fusion (2), with no phoneme shift observed.